2003
DOI: 10.1097/00043426-200301000-00007
|View full text |Cite
|
Sign up to set email alerts
|

HER-2/ neu Expression in Osteosarcoma Increases Risk of Lung Metastasis and Can Be Associated With Gene Amplification

Abstract: The purpose of this study was to investigate whether Her-2/neu expression at diagnosis of osteosarcoma could provide biologic and prognostic information that predicts the risk of pulmonary metastases and outcome. Human epidermal growth factor (Her-2/neu) expression in 25 initial pretreatment osteosarcoma biopsies and 12 posttreatment pulmonary metastatic osteosarcoma resection specimens was assessed by standard immunohistochemical techniques on formalin-fixed paraffin-embedded tissue. As a screening analysis t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
83
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(87 citation statements)
references
References 18 publications
2
83
2
Order By: Relevance
“…Some immunohistochemical studies demonstrated a significant correlation between Her-2/neu expression and a poor histologic response to preoperative chemotherapy, a decreased event-free survival as well as an increased risk of pulmonary metastases. [17][18][19]23 In contrast, other studies observed Her-2/neu expression irrespective of histologic subtype and grade that was not associated with response to preoperative chemotherapy and clinical outcome. 22 Further reports did not observe Her-2/neu overexpression or even reported complete absence of Her-2/neu Figure 5 RNA was extracted from the indicated numbers of lasermicrodissected cells obtained from a decalcified, paraffinembedded and formalin-fixed osteosarcoma section and converted to cDNA.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Some immunohistochemical studies demonstrated a significant correlation between Her-2/neu expression and a poor histologic response to preoperative chemotherapy, a decreased event-free survival as well as an increased risk of pulmonary metastases. [17][18][19]23 In contrast, other studies observed Her-2/neu expression irrespective of histologic subtype and grade that was not associated with response to preoperative chemotherapy and clinical outcome. 22 Further reports did not observe Her-2/neu overexpression or even reported complete absence of Her-2/neu Figure 5 RNA was extracted from the indicated numbers of lasermicrodissected cells obtained from a decalcified, paraffinembedded and formalin-fixed osteosarcoma section and converted to cDNA.…”
Section: Discussionmentioning
confidence: 81%
“…21,22 On the other hand, a correlation of cytoplasmic Her-2/neu positivity with a shorter overall metastasis-free survival has recently been reported. 23 These discrepancies have extensively been discussed in the literature and attributed mainly to technical issues including the type of tissue, fixation method, storage conditions, sensitivity and reliability of the antibodies used, the scoring system and the interpretation of the results. 24,22 Owing to the methodical problems concerning immunohistochemical analysis of Her-2/neu, we focused on the evaluation of the prognostic significance of Her-2/neu gene expression on the outcome of osteosarcoma therapy.…”
mentioning
confidence: 99%
“…Moreover, as extensively discussed by Anninga and colleagues (17), inconsistent findings have also been reported with regards to HER2 status and its prognostic significance. In certain studies, the increased levels of the HER2 protein at diagnosis resulted in an association with poor histological response to chemotherapy and/ or a poorer clinical outcome (16), whereas other reports did not show any correlation between HER2 and poor treatment response or prognosis (14).…”
Section: Metastatic Disease Number Of Patients ----------------------mentioning
confidence: 98%
“…Of 12 metastatic samples, all 12 were HER2-positive. In bone tumors, several studies on HER2 have been performed for osteosarcoma and Ewing's sarcoma, the two most common types of neoplasms of the skeleton, but the findings reported thus far are contradictory (13)(14)(15)(16)(17). Particularly for osteosarcoma, the data reported are paradoxical, ranging from studies in which HER2-increased expression was detected in 63% of patients (14) to other studies in which it was uncommon or even absent (13,15,17).…”
Section: Metastatic Disease Number Of Patients ----------------------mentioning
confidence: 99%
“…8 Overexpression of the HER-2 protein has been reported in 10-34% of breast carcinomas 9 and is reported to have prognostic significance. Subsequently, overexpression has been reported in an increasing number of malignancies, including ovarian carcinoma, 10 osteosarcoma, 11 invasive bladder carcinoma, 12 prostate adenocarcinoma, 13 cholangiocarcinoma, 14 primary brain tumors 15 and colon carcinoma, 16 among others. HER-2 protein expression in cutaneous neoplasms has not been well characterized.…”
mentioning
confidence: 99%